2015
DOI: 10.1200/jco.2015.61.6490
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Phase III Randomized Trial of the Antiprogestin Agent Mifepristone in the Treatment of Unresectable Meningioma: SWOG S9005

Abstract: Purpose Progesterone receptors are expressed in approximately 70% of meningiomas. Mifepristone is an oral antiprogestational agent reported to have modest activity in a phase II study. This multicenter, prospective, randomized, placebo-controlled phase III trial conducted by SWOG was planned to define the role of mifepristone in the treatment of unresectable meningioma. Patients and Methods Eligible patients were randomly assigned to receive either mifepristone or placebo for 2 years unless disease progressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 51 publications
(13 reference statements)
1
63
0
Order By: Relevance
“…Most previous anecdotal cases were treated with a 200 mg dosage of mifepristone (1)(2)(3)(4). The drug was very well tolerated consistent with extensive data from patients that used it for the treatment of meningiomas (26). The case presented here, similarly to the first case in the study, showed that the 300 mg dosage of mifepristone is also well tolerated and relatively free of side effects.…”
Section: Discussionsupporting
confidence: 75%
“…Most previous anecdotal cases were treated with a 200 mg dosage of mifepristone (1)(2)(3)(4). The drug was very well tolerated consistent with extensive data from patients that used it for the treatment of meningiomas (26). The case presented here, similarly to the first case in the study, showed that the 300 mg dosage of mifepristone is also well tolerated and relatively free of side effects.…”
Section: Discussionsupporting
confidence: 75%
“…10,21,25,27 The Southwest Oncology Group (SWOG-S9005) completed a phase III trial, published in 2015 by Ji and colleagues, assessing mifepristone, an antiprogestin. This study (SWOG-S9005) randomized patients with progressive or recurrent meningioma to receive either oral mifepristone or placebo, and found no improvement in either failure-free or overall survival with mifepristone.…”
Section: Introductionmentioning
confidence: 99%
“…This study (SWOG-S9005) randomized patients with progressive or recurrent meningioma to receive either oral mifepristone or placebo, and found no improvement in either failure-free or overall survival with mifepristone. 21 …”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical results of mifepristone seem mitigated (Cossu et al, 2015;Ji et al, 2015). Further studies are needed to assess the role of ER stress in anaplastic meningiomas, but the rarity of such lesions limits wide cohort analysis.…”
Section: Er Stress In Primary Brain Cancersmentioning
confidence: 88%